Peran CAR Dalam Memediasi Antara FDR dan NPF Terhadap Profitabilitas - Nabila Amyrtha Putri; Hilda Hilda; Tariza Putri Ramayanti (Departement of Islamic Banking, Faculty of Islamic Economics and Business, The State of Islamic University (UIN) Sultan Maulana Hasanuddin Banten,, 2022)
The purpose of this study was to determine the role of CAR in mediating between FDR and NPF on probility at islamic commercial bank in Indonesia. This research uses quantitative research obtained from quarterly quartely financial reports published form the websites of each islamic commercial bank in Indonesia for the 2016-2020 period. This study used a purposive sampling tecnique obtained 6 samples were obtained form 14 banks with an observation period of 5 years. The data analysis technique uses path analysis with SPSS 21. The result of the data analysis of this study rove that FDR has no effect on CAR, NPF has a negative significant effect on CAR, FDR has no effect on probility, NPF has a negative significant effect on probility, CAR has a positve significant effect on probility, CAR is unable to mediate the effect of FDR on probility, and CAR are able to mediate the effect of NPF on probility.